Internet marketing is a new trend in modern marketing concept. (Journal of Economic Research & Business Administration, 2016)
The emergence and rapid development of the global Internet network has led to the emergence of new communication media, as well as e-commerce market with many buyers and potential customers. The development of communication technologies are currently transforming many processes in the modern society. Is no exception and the business sphere. The rapid development of e-business was the basis for the development of the newest trends in the modern concept of marketing – Internet marketing.Internet marketing is a component of electronic commerce. It is also called online-marketing. It may include such parts as Internet integration, information management, PR, Customer Service and sales.
Keywords: marketing; Internet-Marketing; Internet-shop; information technology; e-business; business-to-business; business-to-consumer; consumer-to-consumer; business administration; consumer-to-administration; online-shopping.